Influence of methodological strategies and didactic resources used by teachers to teach speaking in 8th year ismael perez high school - Ontaneda Maldonado, Nely Elena (Machala : Universidad Técnica de Machala, 2016)
The influence of the methodological strategies and the didactic resources play an important role in the teaching learning process because strategies are considered, according to some authors such as joe valdez , actions that allow to make the class active and productive, succeeding in involving the total students to participate. for that, the suitable didactic resource have to be used, as they are one of the many interactive features of any participative methodology. through a previous investigation done to the 8th year of basic education students in ismael pérez pazmiño high school, it could be noticed that the learning problems and the students speaking skill little practice to communicate are due directly to the lack of methodological strategies application by the teacher and the good didactic resources scarce use, among them, the information and communication technologies tic. it is considered essential, especially in the ismael high school, that the teachers of the english area put in practice such methodological strategies and the right didactic resources when delivering their lessons, that is why with the topic “influence of methodological strategies and teaching resources used by teachers to teach speaking in 8th year of ismael perez high school” the aim is to identify the influence of the methodological strategies and offer the use of tools such as video chat, tandem, langblog, as strategies with the usage of technology as a didactic resource to make the students of the 8th year communicate in english and they can effectively develop the skill of speaking
Keywords: METHODOLOGY; STRATEGY; DIDACTIC; RESOURCE